Diagnóstico de la formación docente de estudiantes de cultura física de la Universidad Luis Vargas Torres de la ciudad de Esmeraldas en función de la atención educativa a la discapacidad sensorial - Estupiñán Caicedo, Bertha Luz (2014)
Today education has not recorded a process of change from providing education to people who have special educational needs related to disability despite that legislation demands it. The struggle of the people to defend their rights especially the education has been admirable. In many establishments providing education for people with special educational needs is very expensive and exclusive, since a budget is required to develop processes to inclusive education of these students, and the training of teachers on this issue and no But could ignore if universities in their curricula contemplate providing education to the disabled population.